Feasibility of Music-Assisted Treadmill Training in Parkinson's Disease Patients With and Without Deep Brain Stimulation: Insights From an Ongoing Pilot Randomized Controlled Trial - Gooßes, Mareike; Saliger, Jochen; Folkerts, Ann-Kristin; Nielsen, Jörn; Zierer, Jürgen; Schmoll, Paula; Niepold, Annika; Colbach, Liz; Leemhuis, Janna; Engels, Lea; van Krüchten, Maria; Ophey, Anja; et al. (Frontiers in Neurology, 2020)
Background: Music-assisted treadmill training (MATT) is a new therapy approach for Parkinson’s disease (PD) patients, combining treadmill training with rhythmic auditory cueing and visual feedback. PD studies have shown larger positive effects on motor outcomes than usual treadmill training. However, effects on cognition, in contrast, are less clear. Existing studies provided intensive training protocols and included only stable medicated patients. Thus, a pilot randomized controlled trial (RCT) was designed to analyze the feasibility of a shorter training protocol as well as preliminary effects on cognition, motor function, and patient-centered outcomes in a rehabilitation setting where PD patients with and without deep brain stimulation (DBS) undergo adaptation of medication and DBS settings. Here, we present the results from the feasibility analysis of the still ongoing trial. Methods: Non-demented PD patients with and without DBS were recruited during their inpatient rehabilitation and randomized to an experimental (EG; 20 min. MATT) or an active control group (CG; 20 min. bike ergometer training). The trainings took place for eight consecutive days and were added to the usual rehabilitation. Feasibility was assessed with the following parameters: patients’ study protocol acceptance, study protocol transferability into clinical routine, training-induced adverse events, and patients’ training perception. Results: 32 patients (EG: n= 15; CG: n= 17; 72% DBS) were included. The study protocol was well accepted (inclusion-rate: 84%). It was transferable into clinical routines, as dropout-rates of 40% (EG) and 18% (CG) were observed. However, in depth analysis of the dropout cohort did not reveal intervention-related dropout-reasons. The MATT as well as the standard ergometer training showed no adverse events and were positively perceived by PD patients with and without DBS. Conclusion: MATT was shown to be a feasible, safe and enjoyable treatment option in PD patients with and without DBS. Furthermore, the dropout cohort analysis revealed some exciting first insights into possible dropout reasons that go beyond the form of intervention. Therefore, research would benefit from a common practice of dropout analyses, as this would enhance our understanding for patients’ therapy adherence and expectations.